APLIKASI LET’S READ SEBAGAI MEDIA MEMBACA NYARING UNTUK ANAK USIA DINI - Rahmawati Mulyaningtyas; Bagus Wahyu Setyawan (ESTETIKA: JURNAL PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2021)
Reading aloud is necessary for early childhood. Reading aloud can help developing language, growing literacy from an early age, increasing intellectual competence, controlling emotions, and bringing parents closer to their children. As technology growing fast, there are many reading materials that can be used in reading aloud. One of the media that can be used in reading aloud is the Let's Read application. Let's Read is a free of charge application in the form of digital books that can be accessed online and offline. This study uses descriptive qualitative method. This study aims to explain the use of the Let's Read application in reading aloud, reading materials that can be used in the Let's Read application to read aloud, and the advantages and disadvantages of the Let's Read application. The results of this study indicate that the Let's Read application can be used on parents' gadgets, such as smart phones or laptops. Reading materials that can be used in reading aloud can be adjusted into the difficulty level of reading material or children's interest in pictures / illustrations. The advantages of this application are that it can be accessed for free, presented in several languages ​​(multilingual), attractive appearance in terms of illustrations and the use of font face or font size (can be enlarged or reduced) as well as the content of story that is easy to comprehend. On the other hand, the disadvantage of this application is on illustrations/ images presented in two dimensions.